Population Genomics and Morphology Provide Insights into the Conservation and Diversity of Apis laboriosa - Ri Liu; Xuntao Ma; Longfu Zhang; Kang Lai; Changbin Shu; Bin Wang; Mingwang Zhang; Mingxian Yang (Insects)
In recent decades, honeybee populations have declined, dramatically owing to destructive honey harvesting practices and the loss of foraging grounds and nesting sites. Among them, Apis laboriosa Smith, 1871 (Hymenoptera, Apidae), an important pollinator species found in the Himalayan region, holds significant economic and ecological value. However, conservation efforts and intraspecific taxonomic studies regarding it have been rather limited, and thus its full geographic range remains elusive. This study is the first to research A. laboriosa in Sichuan. Through a systematic study integrating morphological feature analysis and genomic data, the following conclusions are drawn. Whole-genome resequencing data analysis reveals that the Sichuan population forms a new monophyletic group (Bootstraps = 100). In the past ten thousand years, the population sizes of A. laboriosa in four different regions of China have been decreasing rapidly. Measures should be taken to protect them across the entire distribution range, especially the populations in Tibet and Sichuan, due to their relatively large genetic differences and low intra-population genetic diversity. Based on the significant difference analysis, the following four wing vein morphological features with extremely significant differences were identified: the width of the right forewing (FB), the cubital index a/b (Ci), the forewing vein angle (E9), and the forewing vein angle (K19). These findings are expected to offer a valuable reference for future A. laboriosa conservation endeavors, particularly in protecting populations with a high level of genetic differentiation.